2013
DOI: 10.1161/circulationaha.113.001873
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Diastolic Impairment in Patients With Pulmonary Arterial Hypertension

Abstract: I diopathic pulmonary arterial hypertension (PAH) is a rare but fatal disease with a survival rate of 58% at 3 years. Present therapy is unable to normalize pulmonary arterial pressures, and PAH patients ultimately develop right heart failure. Editorial see p 1999 Clinical Perspective on p 2025Previous studies have demonstrated that PAH patients have reduced systolic function as measured by right ventricular Background-The role of right ventricular (RV) diastolic stiffness in pulmonary arterial hypertension (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
319
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 312 publications
(355 citation statements)
references
References 29 publications
31
319
5
Order By: Relevance
“…improving diastolic stiffness). This could be particularly important as it has been recently demonstrated that patients with PAH-associated RV dysfunction present with significant diastolic dysfunction [50].…”
Section: Study Limitationsmentioning
confidence: 99%
“…improving diastolic stiffness). This could be particularly important as it has been recently demonstrated that patients with PAH-associated RV dysfunction present with significant diastolic dysfunction [50].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Tissue powder was solubilized in 8 M urea buffer with DTT and 50% glycerol solution with protease inhibitors (0.16 mmol/l leupeptin, 0.04 mmol/l E-64, and 0.2 mmol/l PMSF). Samples were loaded in triplicate on 1% agarose gels stained with SYPRO Ruby to determine titin isoform composition as described previously (27).…”
Section: Human Myocardial Tissuementioning
confidence: 99%
“…A collaboration between colleagues in Amsterdam, Paris, and Arizona (Rain et al 2013) using SHB samples concluded that a combination of changes in titin stiffness, reduced cTnI phosphorylation, and altered levels of phosphorylation of Ca 2+ -handling proteins all contribute to RV diastolic dysfunction in PAH. The following year, Manders et al (2014) used cardiac MRI, to show that the RV in PAH (both idiopathic and PAH in Eisenmengers syndrome patients) also reduces LV wall thickness, causing a 30% decrease in the ratio of myosin:actin in cardiomyocytes, and significantly reduced protein phosphorylation.…”
Section: Right Ventricular Heart Failurementioning
confidence: 99%